E-Learning Berbasis Jejaring Whathapp pada Matematika - Asima Rohana (Edumaspul: Jurnal Pendidikan, 2022)
Abstract Today, in the modern era, the information technology has very rapid development, especially in the education field, the use of the internet in continues growing... E-learning is a form of learning that utilizes electronic devices, whether using internet access or not.. In the field of education itself, the use of internet access has been widely used for the use of both applications and systems as learning media. The continuity of the education and learning process during the COVID-19 pandemic provides new activities for learning which is not being limited by space or time...Thhe Whatsapp application can be used as a learning media according to the needs and agreements of the teacher and students.. They can also create a certain group to join the students and teachers. Whatsapp as E-Learning is able to create a conducive academic atmosphere as it can be used everywhere and everytime. Its implementation in learning process is also able to present a relaxed learning atmosphere, thus can create the closeness emotionally. Through the group on the Whatsapp application, teachers and students can carry out discussion activities.. In this paper, the write is going to try to describe how useful Whatsapp is in supporting students distance learning, the obstacles which are faced by the teachers and students as well, and what are the advantages of this application Keyword : E-Learning, Whatsapp, Covid 19, mathematics